Piezo-dependent surveillance of matrix stiffness generates transient cells that repair the basement membrane. - Stricker, A.M.; Hutson, M.S.; Page-McCaw, A. (Developmental Cell, 2025)
Basement membranes are extracellular matrix sheets separating tissue layers and providing mechanical support, and collagen IV (Col4) is their most abundant structural protein. Although basement membranes are repaired after damage, little is known about repair, including whether and how damage is detected, what cells repair the damage, and how repair is controlled to avoid fibrosis. Using the intestinal basement membrane of adult Drosophila as a model, we show that after basement membrane damage, there is a sharp increase in enteroblasts transiently expressing Col4, termed "matrix mender" cells. Enteroblast-derived Col4 is specifically required for matrix repair. The increase in matrix mender cells requires the mechanosensitive ion channel Piezo, expressed in intestinal stem cells. Matrix menders are induced by the loss of matrix stiffness, as specifically inhibiting Col4 crosslinking is sufficient for Piezo-dependent induction of matrix mender cells. Our data suggest that epithelial stem cells control basement membrane integrity by monitoring stiffness.